Postoperative Analgesia Efficiency Comparison between Local Infiltration Analgesia and Adductor Canal Block for Postoperative Analgesia in Total Knee Arthroplasty - ทั้งทอง สตบงกช; บ้านไร่ นิภา (Journal of Health Science of Thailand, 2024)
Post operative pain after total knee arthroplasty (TKA) ranging from moderate to severe can impact the recovery process and physical therapy. Local infiltration analgesia (LIA) and adductor canal block (ACB) have been identified as promising methods for pain control. We aimed to compare their efficacy and outcomes in patients undergoing TKA. In this This prospective randomized controlled trial involved 82 patients undergoing unilateral total knee replacement surgery according to a predetermined schedule. They were divided into two groups, with 41 patients each: LIA group and ACB group. Primary outcome was total morphine consumption over postoperative 24 hours. Other comparating variables included visual analog pain scale, time to first and total dosage of rescue analgesia, and postoperative nausea and vomiting. It was found that the first 24 hours tramadol consumption in the LIA group was statistically significantly higher than in the ACB group, which was 60.98 mg and 23.17 mg, respectively. The time to first request tramadol in ACB group was significantly lengthier than in the LIA group, which was 1,226.10 minutes and 913.17 minutes, respectively. The median pain scores during the 12 and 24 hours post-operative of the LIA group were statistically significantly higher in the ACB group. Thus, ACB is more effective in controlling postoperative pain within the first 24 hours after total knee arthroplasty.